1995
DOI: 10.1002/nau.1930140403
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of “subjective” and “objective” measures of severity of urinary incontinence in women

Abstract: The aims of this study were to compare "subjective" measures of severity of urinary incontinence to similar "objective" measures, establish their statistical correlation, and determine the effect of specific urodynamic diagnosis on such correlations. Baseline data was available from 265 women entered into a clinical trial studying pharmacologic and behavioral interventions for urinary incontinence. The "subjective" measures of incontinence were obtained by patient recall during history taking and included: the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
3

Year Published

2000
2000
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 7 publications
1
23
0
3
Order By: Relevance
“…We also found that the gold standard highly correlated with the recall data and diary data regardless of diary length.Thus, if the diary length were to be determined solely on the basis of such correlation analysis, then no obvious diary length could be recommended, and perhaps the use of recall data would be justi¢ed [Elser et al, 1995]. In fact, previous investigations have recommended a diary length varying from anywhere from 1 day to 7 days [Robb, 1985;Wyman et al, 1988;Larsson and Victor, 1992;Barbara et al, 1994;Abrams and Klevmark, 1996;Lose et al, 1998;Gisolf et al, 2000;Groutz et al, 2000;Nygaard and Holcomb, 2000].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…We also found that the gold standard highly correlated with the recall data and diary data regardless of diary length.Thus, if the diary length were to be determined solely on the basis of such correlation analysis, then no obvious diary length could be recommended, and perhaps the use of recall data would be justi¢ed [Elser et al, 1995]. In fact, previous investigations have recommended a diary length varying from anywhere from 1 day to 7 days [Robb, 1985;Wyman et al, 1988;Larsson and Victor, 1992;Barbara et al, 1994;Abrams and Klevmark, 1996;Lose et al, 1998;Gisolf et al, 2000;Groutz et al, 2000;Nygaard and Holcomb, 2000].…”
Section: Discussionmentioning
confidence: 96%
“…Recall data are not necessarily unreliable [Elser et al, 1995]; however, a frequency-volume chart or a frequency diary is nowadays recommended to accurately measure the symptom [Lose et al, 1998]. Diary recordings have been con¢rmed to be reproducible and more accurate compared with patient's recall [Wyman et al, 1988;Larsson and Victor, 1992;McCormack et al, 1992;Groutz et al, 2000;Nygaard and Holcomb, 2000;Blanker et al, 2000].…”
Section: Introductionmentioning
confidence: 99%
“…Incongruence of self-reported vs. clinician-reported measures of functionality or severity can be seldom found in the medical literature (Cowen, Wakefield, & Cloutier, 2007;Elser & Fantl, 1995;Schrader, 1997), but are rarely explored more in depth. To our knowledge, it is the first time this topic is analysed among patients with gastrointestinal pathologies.…”
Section: This Is the First Study Comparing Different Psychological Anmentioning
confidence: 99%
“…Use of diaries as an objective tool is strongly advocated by the medical community [17, 18]. Patients used diaries at baseline and at each follow–up visit to document the amount voided, leaked or catheterized for every episode for a minimum of 3 days.…”
Section: Study Design and Methodsmentioning
confidence: 99%